Enhancing adherence to clinical practice guidelines for hypertension management: Evaluation of the effectiveness of a Hypertension Management Tool Kit (HMTK) among primary healthcare doctors. (ImprovBP-HMTK) - Manoharan, Anusha; Ngee Ling, Beatrice Jee; Hazwan, Mat Din; Salbiah, Mohamed Isa; Norasnita, Nordin; Tan, Siow Foon; Ho, Bee Kiau (Clinical epidemiology and global health, 2024)
Adherence to guidelines in managing hypertension among primary healthcare doctors remains suboptimal. We assessed the effectiveness of a Hypertension Management Tool Kit (HMTK) in improving guideline adherence. Medical records of 392 patients attending 2 primary care clinics in the Klang district with 3 or more anti-hypertensive medications were audited. Paired T-test and repeated measure ANOVA were used to evaluate the effectiveness of the HMTK intervention with the evaluation of interaction within-subject effects, between subject effect and time. The mean MOGC score of doctors with <5 years of service was 79.765 (95 % CL 78.351,81.178) and with >5 years of service; 81.238 (95 % CI 80.621,81.855). Statistically significant (p-value <0.001) results were shown based on the time effect and mean MOGC score with HMTK; pre-intervention 72.426 (95%CI 71.045, 73.808) and post-intervention 88.576 (95 % CI 87.922, 89.230). The mean MOGC score post-intervention based on the time effect and years of service for both groups were statistically significant (p-value <0.001) and increment was shown in <5 years of service; 69.252 (14.915) to 87.149 (6.484) while >5 years of service; 73.485 (14.281) to 89.613 (5.149). Statistically significant was shown by years of service in time-group interaction effect pre- and post-intervention (p-value <0.001); pre-intervention for <5 years of service; 71.892 (95%CI 69.339,74.446) and >5 of service; 72.960 (95 % CI 71.895,74.075). Post-intervention in <5 years of service; 87.692 (95%CI 86.427,88.846) while >5 years of service; 89.516 (95%CI 88.987,90.044). The HMTK is an effective tool to improve the management of hypertension among doctors.